Sistem Informasi Pencocokan Data Pemilih Berbasis Web Pada Kantor KPUD Kabupaten Pangkep - Suryadi Syamsu (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2021)
There is still inaccurate voter data such as duplicate data, underage and inefficient recapitulation processes. The aims of the study was to reduce inaccurate voter data and to streamline the time of the recapitulation process. The proposed system is a web-based voter data matching system in Pangkep Regency KPUD office. The data was obtained through (1) Field Research, (2) interviews.The research method used is the profile matching method on voter data. The testing technique uses a black box and a questionnaire. The results of the study indicate that thebased voter data matching system at the KPUD Pangkep Regency Office web produces accurate voter data, streamlines the time of the recapitulation process.